1879 N.C. Sess. Laws 231, ch. 127, §§ 1-2 - (:unkn) unknown (General Publisher, 1879)
Prohibited the concealed carry of any pistol, Bowie-knife, dirk, dagger, slung-shot, loaded cane, brass knuckles, iron knuckles, metal knuckles, or other deadly weapon of a like kind. Violators guilty of a misdemeanor.
--
Keywords: CARRY - CONCEALED